ANALISIS PERILAKU HIKIKOMORI PADA TOKOH TAMOTSU TADOKORO DALAM MANGA FUTSUTSUKA MONO NO ANI DESU GA KARYA HIGURASHI KINOKO - Dinda Puan Maharani; Ari Artadi; Riri Hendriati (IZUMI, 2024)
Hikikomori is one of the social problems in Japan. A research on the hikikomori behavior of Tamotsu Tadokoro in Higurashi Kinoko's Manga Futsutsuka Mono no Ani Desu ga was conducted. The purpose of this research is to know and explain the forms of behavior, and factors that cause hikikomori behavior and to find out and explain the efforts made by the character Tamotsu Tadokoro in the Comic series "Futsutsuka Mono no Ani Desu ga" by Higurashi Kinoko to try to get out of hikikomori behavior. The research method used is descriptive qualitative by analyzing media data in the form of comic series based on Saito Tamaki's theory of Hikikomori Behavior, Michael J. Dziesinski's theory of Social Factors that cause hikikomori behavior, and David McClelland's Theory of Motivation. The results showed that Tamotsu Tadokoro experienced seven symptoms of hikikomori behavior and was caused by school environment, family, and individual factors. In addition, Tamotsu Tadokoro was able to successfully emerge from hikikomori behavior because he was motivated to improve his relationship with his family and pursue his goals. Therefore, it can be proven that Tamotsu Tadokoro can be labeled as a hikikomori. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor